Cultural issues in adventure programming: applying Hofstede's five dimensions to assessment and practice. Issue 4 (2nd October 2017) - Chang, Te-Hsin; Tucker, Anita R.; Norton, Christine Lynn; Gass, Michael A.; Javorski, Stephen E.
ABSTRACT: Adventure programming has seen considerable growth throughout the world. While newly established programs aim to meet the needs of their prospective clients, failing to account for cultural differences when conducting or designing programs may impede this goal. Non-western approaches to implementing adventure programs have rarely been discussed, because there is a lack of a clear theoretical framework for addressing cross-cultural issues in adventure programming. This article seeks to address these limitations by drawing attention to the existing literature on the impact of cultural differences on adventure programming and relevant fields (e.g. education), providing suggestions for how such theories could inform facilitation styles. It is proposed that a model adapted from the work of Hofstede offers one useful framework for assessing groups from different cultural contexts, which can strengthen the practice of adventure programs to better meet the needs of participants.